Medication adherence by heart failure patients before and after pharmacotherapeutic follow-up at a clinical center specialized in cardiology in Rio de Janeiro / Adesão à medicação por pacientes com insuficiência cardíaca antes e depois do acompanhamento farmacoterapêutico em um centro clínico especializado em cardiologia no Rio de Janeiro - Camuzi, Ranieri Carvalho (2022)
Objective: to analyze adherence data by self-report, and factors related to adherence of patients monitored by a multidisciplinary team in a specialized and referral center in cardiology in the public health network. Method: descriptive cross-sectional study of the records considered at moments 0 and 4 months. Result: initially included 57 patients ≥18 years old, diagnosed with heart failure with reduced ejection fraction, mean age 55 years, 66.7% male, 75.4% NYHA functional class I / II, most polymedicated and treating 2 or more comorbidities. At 0 and 4 months, good adherence was reported by 22.8% and 29.3% of patients, respectively; the most frequent attitude of non-adherence was forgetting to take and neglecting the time to use the medications, respectively. Several associated factors have a statistically significant relationship with adherence. Conclusion: there was only 1 patient with adherence out of 4. When intervening with a pharmacotherapeutic follow-up strategy, after 4 months, an improvement in the adherence score of 1 patient out of 4 was observed, indicating that the pharmacist's role could cause a change in adherence behavior.